Different approaches in the treatment of obstructive pulmonary diseases - Kabir, Eva Rahman; Morshed, Nabila (© 2015 Elsevier, 2016)
This article was published in European Journal of Pharmacology [© 2015 Elsevier] and the definite version is available at http://www.sciencedirect.com/science/article/pii/S0014299915301564 The article website is at: http://www.sciencedirect.com/science/journal/00142999/764/supp/C